2015 IEEE 65th Electronic Components and Technology Conference (ECTC) 2015
DOI: 10.1109/ectc.2015.7159785
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a novel low cost single material temporary bond solution for high topography substrates based on a mechanical wafer debonding and innovative adhesive removal

Abstract: Among the technological developments pushed by the emergence of 3D-ICs, wafer thinning has become a key element in device processing over the past years. As technology matures, more emphasis is now being put on the overall cost of ownership, which is still regarded as a refraining element for technology adoption. Therefore novel temporary bond concepts and materials are being explored to further bring down the process complexity and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…TGA results showed that the material decomposes at 360 • C with 0.5% [60]. A via-middle integration flow with a 50 µm high Cu pillar has been demonstrated [51,79]. The adhesive is about 30 µm thick, while the wafer is thinned to 50 µm with a total thickness variation (TTV) value of about 2 µm in this progress.…”
Section: Mechanical Peel-offmentioning
confidence: 80%
“…TGA results showed that the material decomposes at 360 • C with 0.5% [60]. A via-middle integration flow with a 50 µm high Cu pillar has been demonstrated [51,79]. The adhesive is about 30 µm thick, while the wafer is thinned to 50 µm with a total thickness variation (TTV) value of about 2 µm in this progress.…”
Section: Mechanical Peel-offmentioning
confidence: 80%